Impact of COVID-19 on chronic lung disease in children: Asthma and cystic fibrosis - Laura-Larisa Dracea (Amaltea Medical Publishing House, 2020)
In December 2019, the WHO identified a novel coronavirus that leads to severe acute respiratory syndrome (SARSCoV-2). COVID-19, the disease produced by the novel coronavirus, seem to less affect children and cause severe disease compared to adults, being associated with lower case-fatality rates. Asthma and cystic fibrosis (CF) are the most common chronic lung diseases that affect children and adolescents. It is not well established if there is a higher risk of poor outcomes due to infection with SARS-CoV-2. Research that demonstrated that the angiotensin-converting enzyme 2 (ACE2) receptor required for coronavirus recognition and infection may be under-expressed in airways of atopic children, led to a paradox that sets asthma as being a protective condition for COVID-19. Patients with CF manifest cytokine dysfunction and chronic inflammation enhanced by the diversity of pathogens in the airways, mechanisms that overlap with the pathophysiology of COVID-19. International data suggest that very few CF patients experienced symptoms and complications due to COVID-19 and, if the disease is milder than anticipated in CF, this could be related to some protection due to the cellular effect of CFTR mutations associated with viral processing. Taken together, asthma and cystic fibrosis, chronic diseases with significant impact on morbidity and mortality in both children and adults, may serve as a model of factors that may mitigate the impact of SARS-CoV-2 and creates opportunities for developing research.